Role of ERK1/2 and JNK phosphorylation in iodine contrast agent-induced apoptosis in diabetic rat kidneys. (14th September 2015) - Jiao, Zhanquan; Chen, Jun; Liu, Yanhong; Liu, Tong; Chen, Kangyin; Li, Guangping
Abstract: Background : The risk of contrast-induced acute kidney injury (CIAKI) is significantly increased in patients with diabetes mellitus. This study aimed to investigate molecular mechanisms of contrast media-induced apoptosis in diabetic rat kidneys, especially the involvement of ERK1/2 and JNK signal pathways. Methods : Diabetic Sprague–Dawley rats were induced by intraperitoneal injection of streptozotocin. Ten weeks later the normal and diabetic rats were administered high-osmolar contrast media (HOCM; meglumine diatrizoate) or normal saline (10 mL/kg) injection for 2 consecutive days. At 24 h after the operation, the rats were sacrificed, the blood samples were collected for examining serum creatinine and the kidneys were collected for determining the expression of caspase-3 by immunohistochemistry and the expression of Bcl-2, Bax, upstream signal molecule p-JNK, and p-ERK1/2 by western blotting. Results : The serum creatinine was significantly increased in diabetes + contrast media group (DC group) after operation compared with in the diabetic group (D group; 103.89 ± 9.01 μmol/L vs. 71.52 ± 7.03 μmol/L, p <  0.05). While creatinine clearance rate (Ccr) was significantly decreased in DC group after operation (1.49 ± 0.33 mL/min vs. 2.60 ± 0.54 mL/min, p <  0.05). Especially, in the diabetic kidney, the expression of caspase-3 was also significantly increased after intravenous injection of HOCM compared with normal saline. The expression level of upstream signal molecule p-JNK protein was apparently increased, but p-ERK1/2 protein was significantly decreased (both p <  0.05). Conclusions : The ionic HOCM-induced renal cells apoptosis in diabetic rats through activating the caspase-3 apoptotic pathway, which might be mediated by upstream MAPK (inhibiting p-ERK1/2 expression and promoting p-JNK expression) signal pathways.